Possible effects of sodium chloride treatment on quality of effluents from Alabama channel Catfish ponds - Sipaúba Tavares, Lúcia H. [UNESP]; Boyd, Claude E. (Wiley, 2003)
Channel catfish ponds are treated with salt (sodium chloride) to increase chloride concentration and prevent nitrite toxicity in fish. A survey indicated that most farmers try to maintain chloride concentration of 50 to 100 mg/L in ponds by annual salt applications. Averages and standard deviations for selected water quality variables in salt-treated ponds were as follows: chloride, 87.2 ± 37.5 mg/L; total dissolved solids (TDS), 336 ± 96 mg/L; specific conductance, 512 ± 164 μmhos/cm. Maximum values were 189 mg/L for chloride, 481 mg/L for TDS, and 825 μmhos/cm for specific conductance. Good correlations between specific conductance values and both chloride and TDS concentrations suggest that specific conductance can be a rapid method for estimating concentrations of these two variables in surface water. The maximum limit for chloride concentration in Alabama streams allowed by the Alabama Department of Environmental Management is 230 mg/L. The usual recommended upper limit of TDS for protection of aquatic life in freshwater streams is 1,000 mg/L. Based on the observed relationship between TDS concentration and specific conductance in Alabama catfish ponds, 1,000 mg/L TDS corresponds to 1,733 μmhos/cm specific conductance. It is unlikely that effluents from salt-treated catfish ponds would violate the in-stream chloride standard of 230 mg/L or harm aquatic life in streams. Nevertheless, chloride concentrations in ponds should be measured before salt application as a safe guard against excessive salt application and chloride concentrations above the in-stream chloride standard.
Keywords: aquaculture effluent; aquaculture method; fish culture; sodium chloride; water quality; water treatment; United States; catfish; Ictalurus; Ictalurus punctatus